Evaluasi Tata Kelola Teknologi Informasi Pada Dinas Komunikasi dan Informatika (DISKOMINFO) Kota Probolinggo Menggunakan Framework COBIT 4.1 Domain Deliver and Support (DS) dan Monitor and Evaluate (ME) - Restu Pambudi; Suprapto Suprapto; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Dinas Komunikasi dan Informatika (Diskominfo) Kota Probolinggo is a government agency and responsible for communication, informatics, statistics, and encryption. According to interview there are some problems encountered in Diskominfo such as some activity are not supported by documentation and SOP for providing service IT, lack of human resource management cause inapproriate assigment to their basic tasks and functions, in addition the evaluation is still for finances and not for information technology, therefore it is needed to evaluate for IT governance to finding the solutions to these problems. In this research will talk about IT governance using COBIT 4.1 framework focus on Deliver and Support (DS) and Monitor and Evaluate (ME) domain. The purposes of this research are assessing current maturity level on domain Deliver and Support and Monitor and Evaluate and giving recommendation to achieve expected maturity level. On Deliver and Support domain the average of current maturity level is 1,61 and for Monitor and Evaluate domain the average of current maturity level is 1,25. The purpose of recommendations is to improve current maturity level so Diskominfo can improve their IT governance, one of the given reccomendation is documenting and socializing for the trainning program that has been done.